COMPARATIVE STUDY OF THE LOADING AMOUNT OF DRUG WITHIN MESOPOROUS SILICA WITH VARIOUS PORE SIZE - AULIFA, DIAH LIA; BUDIMAN, ARIF (International Journal of Applied Pharmaceutics, 2022)
Objective: The loading of drugs into mesoporous silica (MS) is an effective strategy to improve the solubility of poorly water-soluble drugs. Previous reports have stated that the surface area and pore volume of MS can affect drug loading and its crystallization in MS. Therefore, this study aims to elucidate the effect of MS pore size on the maximum drug loading and its dissolution profile. Methods: The ritonavir (RTV) and itraconazole (ITZ) were encapsulated-MS using the solvent evaporation method. The RTV and ITZ loaded-MS were characterized using differential scanning calorimetry (DSC) and PXRD measurement. Results: The amorphization of RTV loaded-MPS and ITZ loaded-MPS were confirmed as a halo pattern in the powder X-ray diffraction pattern. The melting peak and the glass transition of RTV and ITZ were not discovered in MS with the pore size of 80 Å (weight ratio of 3:7), while in the RTV and ITZ loaded-MS with the pore size of 45 Å, the melting peak and the glass transition were observed. This indicated that the loading amount of RTV and ITZ with larger pore sizes is higher than the lower sizes. Conclusion: This study demonstrated that the pore size of MS has a significant effect on the loading amount of drugs in MS.